(untitled) (European Journal of Pure and Applied Mathematics, 2017)
The aim of this paper is to establish some results about the existence and uniqueness of n-tupled fixed point that extends the previous results, using the concept of an α-series for sequence of mappings having mixed monotone property in the framework of ordered complete metric spaces.Â The main result is supported with the aid of an illustrative example.